Harnessing the digital technologies for reaching the unreached: Case of pulse crops - Sah, Uma; Devraj,; Ojha, Jitendra; Dixit, G P (Indian Farming, 2024)
The digital ecosystem of India is witnessing an exponential growth, offering numerous advantages to different sections of society. Digital initiatives in current times have completely revolutionized the information flow in cost and time effective manner in unprecedented ways, changing people’s lives in every sphere. Indian Agriculture has also been impacted by the digital revolution, ushering in positive changes in farmers’ capacities for taking informed decisions in timely manner. This article describes the digital tools employed by IIPR for reaching the farmers.